2019
DOI: 10.1016/j.anai.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Asthma exacerbation trajectories and their predictors in children with incident asthma

Abstract: Background: Asthma exacerbation trajectories in children after incident asthma diagnosis are understudied. Objective: To identify trajectories of asthma exacerbation and predictors of these trajectories in children with incident asthma. Methods: Children from the National Longitudinal Survey of Children and Youth, Canada, with incident asthma were followed-up for up to 12 years during childhood. Latent class growth modeling was used to identify distinct asthma exacerbation trajectory groups. Multinomial logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…1 It is one of the most common chronic illnesses in children, 2 3 presents with periodic exacerbations and remissions, and accounts for substantial medical and economic burden. 4 Global studies of asthma in children have reported that the prevalence of asthma symptoms has increased in the last few decades, which is concerning. 5 Australia is one of the developed countries where asthma continues to be a significant public health concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It is one of the most common chronic illnesses in children, 2 3 presents with periodic exacerbations and remissions, and accounts for substantial medical and economic burden. 4 Global studies of asthma in children have reported that the prevalence of asthma symptoms has increased in the last few decades, which is concerning. 5 Australia is one of the developed countries where asthma continues to be a significant public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…These include transient asthma, early-onset chronic asthma, late-onset chronic asthma and no asthma from early childhood to adolescence. 4 24 25 28 One study described the trajectories as low progressive, early transient and early persistent asthma symptoms. 24 All studies showed that the prevalence was high at 2–5 years of age for all unfavourable types of asthma symptoms trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the data in our study was high as it was based on objective measures of, for example, height, weight, lung function, FeNO, atopic comorbidity and registrations in the patient's medical and pharmacy files of prescription of asthma controllers, OCS, treatment adherence as well as outpatient contacts, ED and hospital admissions. This is an advantage compared with studies using similar exposures and outcomes based on surveys or information by parents, which is more prone to recall bias 2,19,20 . However, it is a limitation that some previously identified risk factors in larger studies could not be included in this retrospective study, for example, previous exacerbations, environmental triggers such as allergens and tobacco exposure, 5,12,21 and socioeconomic status 4,22 …”
Section: Discussionmentioning
confidence: 99%
“…This is an advantage compared with studies using similar exposures and outcomes based on surveys or information by parents, which is more prone to recall bias. 2,19,20 However, it is a limitation that some previously identified risk factors in larger studies could not be included in this retrospective study, for example, previous exacerbations, environmental triggers such as allergens and tobacco exposure, 5,12,21 and socioeconomic status. 4,22 A significant strength of our study is the long-term design with 5 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Exacerbation cohorts may provide useful information on pathomolecular interactions, which can be used for the definition of biomarkers [ 52 , 53 , 54 ]. However, data from exacerbation cohorts of children with asthma are still scarce [ 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%